The anodic stripping voltammetry of nanoparticles: electrochemical evidence for the surface agglomeration of silver nanoparticles. - Toh, H; Batchelor-McAuley, C; Tschulik, K; Uhlemann, M; Crossley, A; Compton, R (2013)
Analytical expressions for the anodic stripping voltammetry of metallic nanoparticles from an electrode are provided. First, for reversible electron transfer, two limits are studied: that of diffusionally independent nanoparticles and the regime where the diffusion layers originating from each particle overlap strongly. Second, an analytical expression for the voltammetric response under conditions of irreversible electron transfer kinetics is also derived. These equations demonstrate how the peak potential for the stripping process is expected to occur at values negative of the formal potential for the redox process in which the surface immobilised nanoparticles are oxidised to the corresponding metal cation in the solution phase. This work is further developed by considering the surface energies of the nanoparticles and its effect on the formal potential for the oxidation. The change in the formal potential is modelled in accordance with the equations provided by Plieth [J. Phys. Chem., 1982, 86, 3166-3170]. The new analytical expressions are used to investigate the stripping of silver nanoparticles from a glassy carbon electrode. The relative invariance of the stripping peak potential at low surface coverages of silver is shown to be directly related to the surface agglomeration of the nanoparticles.